Social and economic consequences of the cost of obstetric and neonatal care in Lubumbashi, Democratic Republic of Congo: a mixed methods study - Musau Nkola Angèle; Ntambue Mukengeshayi Abel; Omewatu Mungomba Jacques; Mundongo Tshamba Henri; Malonga Kaj Françoise (BMC, 2021)
Abstract Background The aim of this study was to explore and measure the social and economic consequences of the costs of obstetric and neonatal care in Lubumbashi, the Democratic Republic of Congo. Methods We conducted a mixed qualitative and quantitative study in the maternity departments of health facilities in Lubumbashi. The qualitative results were based on a case study conducted in 2018 that included 14 respondents (8 mothers of newborns, 2 accompanying family members and 4 health care providers). A quantitative cross-sectional analytical study was carried out in 2019 with 411 women who gave birth at 10 referral hospitals. Data were collected for one month at each hospital, and selected mothers of newborns were included in the study only if they paid out-of-pocket and at the point of care for costs related to obstetric and neonatal care. Results Costs for obstetric and neonatal care averaged US $77, US $207 and US $338 for simple, complicated vaginal and caesarean deliveries, respectively. These health expenditures were greater than or equal to 40% of the ability to pay for 58.4% of households. At the time of delivery, 14.1% of women giving birth did not have enough money to pay for care. Of those who did, 76.5% spent their savings. When households did not pay for care, mothers and their babies were held for a long time at the place of care. This resulted in the prolonged absence of the mother from the household, reduced household income, family conflicts, and the abandonment of the home by the spouse. At the health facility level, the increase in length of stay did not generate any additional financial benefits. Mothers no longer had confidence in nurses; they were sometimes separated from their babies, and they could not access certain prescribed medications or treatments. Conclusion The government of the DRC should implement a mechanism for subsidizing care and associate it with a cost-sharing system. This would place the country on the path to achieving universal health coverage in improving the physical, mental and social health of mothers, their babies and their households.